ECOCRITICISM DISCOURSE IN CLOUDY WITH A CHANCE OF MEATBALLS 2 MOVIE - Neisya, Neisya; Muhammad Fitriansyah, Abdillah; Aprilia, Fitria (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
The ecological theme in literary works is continuing become a popular discourse to increase public awareness about the importance of protecting earth. Animated films are one of the medias for introducing this theme to people, especially children, because it can educate them in an easier way and more interesting. This research endeavors to explore the ecological dimensions and ethical reflections intertwined within the animated film